Mandonismo, Coronelismo, Clientelismo: Uma Discussão Conceitual - Carvalho,José Murilo de (1997)
The literature on Brazilian politics makes broad and frequent use of the concepts of mandonismo, coronelismo, clientelismo, patrimonialism, and feudalism. However, the explanatory power of these concepts has been jeopardized by the imprecise (and at times contradictory) way in which they are often employed. The article points out how these terms are misused and suggests definitions that distinguish one concept clearly from another while accounting of their interrelationships. Each term is also linked to a specific historical moment.